The Universe: Search for Neutrino on Earth (British Journal of Multidisciplinary and Advanced Studies, 2023)
Our planet is bombarded with trillions of particles, from Space from all direction called “Cosmic Rays”. The cosmic rays are made of tiny ‘elementary” particles such as photon, He, Neutrinos, Hydrogen and atomic nuclei have wide range of energies. Cosmic rays high energies suggest that they must be produced in the most energetic processes in the universe. As the cosmic rays particles have net electric charges they get deflected due to presence of geomagnetic fields during their travel and therefore do not travel in straight line. Cosmic rays particles can interact with matter and radiates at the sources to produced extremely particles called neutrino. Gamma rays radio Bursts of Electromagnetic energy in the form of gamma rays are the absolute, most energetic sources of energy known in the universe. The amount of energy that gamma ray bursts puts out in a few seconds is more than the Sun. every will in its entire life time.The neutrino, a fundamental elementary particles of nature, was born out of necessity to keep the conversvation of energy principle. In observed alpha,beta,and gamma decay. Although neutrinos are mot massless like photon of light, they have very special property. Neutrino are omnipresent in nature pass through every square centimeter of bodies without ever notice. Neutrino originate from events in the Universe such as Colloding of Black Holes,Gamma Ray Bursts from exploding stars and or violent event at core of distant Glaxies. A high energy of particles neutrino transform in to it’s particles lepton(electron,muon,ortauon).most accelerated Neutrino beam can also called muons , and few can create tauons. A detector which distinguished among these leptons can reveal the flavor of neutrino incident to charged particle current interaction because interaction involves the exchange of Boson the ‘target’ particle also change (e.g. neutron-proton).Netrinos detectors  is a physics apparatus which is degined to study neutrinos, because neutrinos only weakly interact with other particles of matter, neutrino detector must very large to detect significant number of neutrinos. Confirmed extraterrestrial sources such as Sun,Super Nova1987A,